Financial Feasibility and Marketing Strategy of Hydroponic Romaine Lettuce (Lactuca Sativa L.) (Case Study At Cv. Citra Sehat Organik) - Nur'Aldi, Muhammad Farhan; Masithoh, Siti; Mubarokah, Syaima Lailatul (Universitas Djuanda, 2025)
The aim of this research is to determine business performance, analyze the financial feasibility of hydroponic romaine lettuce farming and marketing strategies at CV. Organic Healthy Image. The method for determining respondents used purposive sampling, namely 4 employee respondents at CV. Organic Healthy Image. The data analysis method in this research uses descriptive analysis and quantitative analysis. with the NPV, Net B/C Ratio, Gross B/C, IRR, Payback Period method using Microsoft Excel, while the marketing strategy includes Segmenting, Targeting, Positioning and marketing mix. The research results show the business performance of romaine lettuce at CV. Organic Healthy Image, namely: financial feasibility analysis shows an NPV value greater than 0 of IDR. 189,384,668, Net B/C more than 1 is 3.69, Gross B/C more than 1 is 1.62, IRR is 130% greater than the discount rate used in this research, namely 10% and payback period is 23 month 24 days, this is declared financially feasible, because the return on investment under the life of the business is 6 years. Marketing strategy implemented by CV. Organic Healthy Image, including (Segmentation, Targeting and Positioning) as well as the 4P marketing mix which includes Product, Price, Place and Promotion has been carried out very well. Products that have labels create attractive packaging, affordable prices, strategic locations and attractive promotions. Implementation of this strategy has proven effective in attracting consumer interest and increasing demand consistently